Epidemiology of balance symptoms and disorders in the community: a systematic review - Murdin, Louisa; Schilder, Anne G M (Otology & neurotology, 2015)
Balance disorders presenting with symptoms of dizziness or vertigo may have significant impact on quality of life and are a recognized risk factor for falls. The objective of this review was to systematically synthesize the published literature on the epidemiology of balance symptoms and disorders in the adult community population. A search was carried out across PubMed, Medline, and Cochrane databases to identify suitable studies. Studies were eligible for inclusion if they contained data on the epidemiology of symptoms of balance disorders (dizziness and vertigo) or balance disorders sampled from community-based adult populations. Data were collected on prevalence and incidence of balance symptoms and on specific balance disorders. A validated risk-of-bias assessment was carried out. Twenty eligible studies were identified. The lifetime prevalence estimates of significant dizziness ranged between 17 and 30%, and for vertigo between 3 and 10%. Published point prevalence data exist for Ménière's disease (0.12-0.5%) and for vestibular migraine (0.98%). For benign paroxysmal positional vertigo, 1-year incidence estimates range from 0.06 to 0.6%. There are no community-based studies on the prevalence or incidence of chronic uncompensated peripheral vestibular disorders or vestibular neuritis. Symptoms of dizziness and vertigo are common in the adult population, and data give a coherent picture of community epidemiology. These data can inform rational service planning and much-needed clinical trials in this field. There are insufficient data on specific balance disorders, especially peripheral vestibular disorders such as vestibular neuritis and its long-term sequelae.